2021
DOI: 10.3892/ol.2021.12845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BRAF‑mediated PI3K/Akt/mTOR pathway on biological characteristics and chemosensitivity of NSCLC A549/DDP cells

Abstract: The present study aimed to explore the biological characteristics of non-small cell lung cancer (NSCLC) cells and the mechanism of chemosensitivity through the role of the PI3K/Akt/mTOR signaling pathway mediated by BRAF gene silencing. Following cell transfection and grouping, an MTT assay detected the activity of NSCLC cells, a scratch wound test assessed the migration ability, flow cytometry using PI staining detected the cell cycle phase, TUNEL and flow cytometry through Annexin V-PI staining assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Yalan Dai et al elucidated that vemurafenib inhibits the immune escape biomarker BCL2A1 by targeting the PI3K/AKT signaling pathway to suppress breast cancer [ 14 ]. BINGNAN REN et al showed that siBRAF inhibits the PI3K/AKT/mTOR signaling pathway synergistically, reducing biological activity while increasing chemosensitivity in non-small cell lung cancer (NSCLC) cells [ 15 ]. However, the precise effect of BRAF on the occurrence and development of ATC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Yalan Dai et al elucidated that vemurafenib inhibits the immune escape biomarker BCL2A1 by targeting the PI3K/AKT signaling pathway to suppress breast cancer [ 14 ]. BINGNAN REN et al showed that siBRAF inhibits the PI3K/AKT/mTOR signaling pathway synergistically, reducing biological activity while increasing chemosensitivity in non-small cell lung cancer (NSCLC) cells [ 15 ]. However, the precise effect of BRAF on the occurrence and development of ATC remains unknown.…”
Section: Introductionmentioning
confidence: 99%